Coordination-induced broadband optical nonlinearity through axial bonding of pyridine anchored methine-bridged polypyrrole to metal-porphyrins. (October 2018) - Wang, Aijian; Zhao, Wei; Chen, Xiaodong; Yang, Yu; Zhu, Weihua; Shang, Danhong
Abstract: A facile route to assemble pyridine anchored methine-bridged polypyrrole to metal-porphyrins through axial bonding has been demonstrated, and the as-prepared nanocomposites exhibit very distinctive broadband nonlinear optical performances compared to their precursors at both 532 and 1064 nm, due to an accumulation effect. Graphical abstract: A facile route to assemble pyridine anchored methine-bridged polypyrrole to metal-porphyrins through axial bonding has been demonstrated, and the as-prepared nanocomposites exhibit very distinctive broadband nonlinear optical performances compared to their precursors at both 532 and 1064 nm, due to an accumulation effect. Highlights: A series of metal-porphyrins functionalized polypyrrole was prepared. Superior broadband optical nonlinearity was observed for the nanocomposites. The central metals of porphyrins obviously influence the optoelectronic responses. The efficient charge transfer responsibles for the improved optical nonlinearity.